Muskuloskeletal Medicines - Hoenig T; Tenforde AS; Hirschmüller A; 4; Cassel M; Rolvien T; Hollander K (Deutsche Zeitschrift für Sportmedizin, 2023)
Bone stress injuries, commonly referred to as stress reactions or stress fractures, are caused by overuse and are prevalent conditions in athletes. These injuries are often seen in sports with high cumulative skeletal loading such as running, athletics, gymnastics, basketball, cricket, or soccer. The main injury pathophysiology is an imbalance between bone microdamage formation and its removal and replacement. A detailed medical history and clinical examination are important for diagnosis, with magnetic resonance imaging representing the gold standard for radiographic confirmation. Treatment and return-to-sport decisions should be individualized and based on injury location, severity, aspects of sports participation, and patient preferences. Initial management includes activity modification, protected weight-bearing, immobilization, optimizing nutrition (caloric intake, dietary calcium, and vitamin D supplementation), and in a few cases surgery. Following initial treatment, progressive loading and return-to-activity are initiated. Overall, a high rate of return-to-sports can be expected. Numerous risk factors that alter bone loading or bone health have been described and their identification is a crucial step towards prevention of future injury.Key Words: Stress Reaction, Stress Fracture, Bone Overuse